The Influence of Leadership Style on Work Discipline of PT Sepakat Citra Mandiri Employees - MM Tri Susetyaning Mildawani (Program Studi Manajemen Institut Manajemen Koperasi Indonesia Bandung, 2023)
The objective of this study is to investigate the impact of leadership style on job discipline. The present study employs an explanatory research design, utilising a quantitative methodology. The sampling technique employed in this study was a non-probability sampling method known as saturated sampling. This method involved selecting all 30 employees of PT Sepakat Citra Mandiri Bekasi as the sample for the study. The employed analysis technique is a straightforward linear analysis technique. The findings of the study indicate that the variable of leadership style has a statistically significant and beneficial impact on employee work discipline. This is evident from the results of the partial test, where the calculated t-value (13.054) exceeds the critical t-value (2.048) at a significance level of 0.001, which is lower than the predetermined threshold of 0.005. The findings of this study indicate that the combined influence of the task behaviour variable and relationship behaviour on employee work discipline accounted for 84.8% of the observed variance. The remaining 15.2% of the variance can be attributed to other variables that were not included as independent variables in this particular research study.